2022
DOI: 10.1186/s40798-022-00450-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Hypoxia–Hyperoxia on Performance- and Health-Related Outcomes in Humans: A Systematic Review

Abstract: Background Intermittent hypoxia applied at rest or in combination with exercise promotes multiple beneficial adaptations with regard to performance and health in humans. It was hypothesized that replacing normoxia by moderate hyperoxia can increase the adaptive response to the intermittent hypoxic stimulus. Objective Our objective was to systematically review the current state of the literature on the effects of chronic intermittent hypoxia–hyperox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 172 publications
1
27
1
2
Order By: Relevance
“…Previous literature supports hypoxia in multiple health conditions (Millet et al, 2016a;Millet and Girard, 2017;Behrendt et al, 2022). More specifically, the safety and efficacy of physical exercises in recovering patients from severe acute respiratory syndrome (SARS) have already been identified but without a detailed description of monitoring variables (Lau et al, 2005).…”
Section: Safety and Effectiveness In The Protocol Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature supports hypoxia in multiple health conditions (Millet et al, 2016a;Millet and Girard, 2017;Behrendt et al, 2022). More specifically, the safety and efficacy of physical exercises in recovering patients from severe acute respiratory syndrome (SARS) have already been identified but without a detailed description of monitoring variables (Lau et al, 2005).…”
Section: Safety and Effectiveness In The Protocol Implementationmentioning
confidence: 99%
“…Hypoxic training has been treated as a promising strategy for health ( Camacho-Cardenosa et al, 2020 ; Behrendt et al, 2022 ), even with the difficulty of establishing an optimal hypoxia dose ( Lizamore et al, 2016 ). Regarding hypoxia as an additional stimulus to exercise and the exercise workload, it is important to control the dose of exposure to hypoxia ( Millet et al, 2016b ; Soo et al, 2020 ; Behrendt et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, intermittent exposure to hypoxia and hyperoxia is expected to have beneficial effects on two of the most common age-related risk factors/comorbidities (i.e., hypertension and dyslipidemia) and is well applicable in geriatric patients. Recently, the effects of IHHE on health-related outcomes have been systematically reviewed, and it has been found that 3–6 weeks of IHHE can reduce cardiovascular risk factors, particularly blood glucose concentration as well as systolic and diastolic blood pressure ( Behrendt et al, 2022b ). However, the evidence concerning the effects of IHHE on blood lipid and lipoprotein concentrations are inconclusive ( Behrendt et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of IHHE on health-related outcomes have been systematically reviewed, and it has been found that 3–6 weeks of IHHE can reduce cardiovascular risk factors, particularly blood glucose concentration as well as systolic and diastolic blood pressure ( Behrendt et al, 2022b ). However, the evidence concerning the effects of IHHE on blood lipid and lipoprotein concentrations are inconclusive ( Behrendt et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%